Alternative splicing adds a new loop to the circadian clock - Petrillo, Ezequiel (2011)
Circadian clocks allow organisms to adjust multiple physiological and developmental processes in anticipation of daily and seasonal changes in the environment. At the molecular level these clocks consist of interlocked feedback loops, involving transcriptional activation and repression, but also post-translational modifications. In a recently published work we provided evidence that PRMT5, a protein arginine methyl transferase, is part of a novel loop within the circadian clock of the plant Arabidopsis thaliana by regulating alternative splicing of key clock mRNAs. We also found evidence indicating that PRMT5 has a role in the regulation of alternative splicing and the circadian network in Drosophila melanogaster, although the clock connection in the latter is more elusive and seems to be at the output level. We conclude that alternative precursor messenger RNA (pre-mRNA) splicing is part of the circadian program and could be a main actor in the fine-tuning of biological clocks. Here, we embrace the alternative splicing process as part of the circadian program and discuss the possibility that this mechanism is of fundamental relevance for the fine-tuning of biological clocks.